Laser ablated titanium oxide nanoparticles in carbon quantum dots solution for detection of sugar using fluorescence spectroscopy - Sadrolhosseini, A. R.; Beygisangchin, M.; Shafie, S.; Rashid, S. A.; Nezakati, Hossein * (IOP, 2021)
Titanium oxide nanoparticles were fabricated using the laser ablation technique in the carbon quantum dots aqueous solution. The ablation time and the particle size were in the range of 2 min to 10 min, and 21.46 nm to 16.07 nm, respectively. The fingerprint peaks and the particle shape in spherical form were obtained from Fourier transform infrared spectrum and transmission electron microscopy, respectively. The optical properties were tested using a UV–visible spectrometer, so the bandgap was obtained in the range of 3.44 eV to 3.7 eV. The prepared sample was used to detect the sugar and the sensitivity of the sample for the detection of glucose is greater than other sugar. The limit of detection is 0.01 ppm.